Progesterone Synthesis in the Nervous System: Implications for Myelination and Myelin Repair - Schumacher, Michael; Hussain, Rashad; Gago, Nathalie; Oudinet, Jean-Paul; Mattern, Claudia; Ghoumari, Abdel (Frontiers in Neuroscience, 2012)
Progesterone is well known as a female reproductive hormone and in particular for its role in uterine receptivity, implantation and the maintenance of pregnancy. However, neuroendocrine research over the past decades has established that progesterone has multiple functions beyond reproduction. Within the nervous system, its neuromodulatory and neuroprotective effects are much studied. Although progesterone has been shown to also promote myelin repair, its influence and that of other steroids on myelination and remyelination is relatively neglected. Reasons for this are that hormonal influences are still not considered as a central problem by most myelin biologists, and that neuroendocrinologists are not sufficiently concerned with the importance of myelin in neuron functions and viability. The effects of progesterone in the nervous system involve a variety of signaling mechanisms. The identification of the classical intracellular progesterone receptors as therapeutic targets for myelin repair suggests new health benefits for synthetic progestins, specifically designed for contraceptive use and hormone replacement therapies. There are also major advantages to use natural progesterone in neuroprotective and myelin repair strategies, because progesterone is converted to biologically active metabolites in nervous tissues and interacts with multiple target proteins. The delivery of progesterone however represents a challenge because of its first-pass metabolism in digestive tract and liver. Recently, the intranasal route of progesterone administration has received attention for easy and efficient targeting of the brain. Progesterone in the brain is derived from the steroidogenic endocrine glands or from local synthesis by neural cells. Stimulating the formation of endogenous progesterone is currently explored as an alternative strategy for neuroprotection, axonal regeneration and myelin repair.